(untitled) (Journal of Forensic Medicine & Toxicology, 2016)
This study aimed to reconstruct stature among male and female Punjabi community of Malwa region using percutaneous measurement of femur length, for estimating the stature, femur length was recorded on each subject using the standard measurement techniques. The data composed of 400 Punjabi subjects within the age range of 20-25 years. Multiplication factors and linear regression equations for stature estimation were determined produced using the above mentioned variables.